1998
DOI: 10.1007/s004670050468
|View full text |Cite
|
Sign up to set email alerts
|

Humoral factor in children with neonatal Bartter syndrome reduces bone calcium uptake in vitro

Abstract: The neonatal Bartter syndrome (NBS) is associated with a complex disorder of mineral metabolism in children, including hypercalciuria, nephrocalcinosis, and diminished bone mineral density. Although cyclooxygenase inhibition usually brings about improvement in these findings, there is a variable component which is resistant to such therapy in many children. The factor mediating this disorder has not been identified. Blood and urine from 12 children with NBS were examined. When compared with samples from normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Recently, we have shown that this bone resorption is associated with the presence of a factor that enhances bone resorption in an in vitro system and produces hypercalcemia in vivo when given intraperitoneally to rats [3]. This factor is a complex of b-FGF and a glycosaminoglycan, and increased bone resorption in vitro and in vivo with b-FGF has been shown by others [10].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Recently, we have shown that this bone resorption is associated with the presence of a factor that enhances bone resorption in an in vitro system and produces hypercalcemia in vivo when given intraperitoneally to rats [3]. This factor is a complex of b-FGF and a glycosaminoglycan, and increased bone resorption in vitro and in vivo with b-FGF has been shown by others [10].…”
Section: Discussionmentioning
confidence: 88%
“…A major thrust of our efforts over the past several years has been to understand the calcium disorder in NBS, characterized by massive hypercalciuria, nephrocalcinosis, and osteopenia [3]. In one of our earliest studies, we showed that untreated children with NBS had significant elevations in 1,25-dihydroxycholecalciferol [8], with corresponding evidence of enhanced enteric calcium absorption.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations